Fasentin diminishes endothelial cell proliferation, differentiation and invasion in a glucose metabolism independent manner - Ocaña, María Carmen; Martínez-Póveda, Beatriz Amparo; Mari-Beffa, Manuel; Quesada, Ana R.; Medina-Torres, Miguel Ángel (Wiley Online Library, 2020)
The synthetic compound fasentin has been described as a modulator of GLUT-1 and GLUT-4 transporters, thus inhibiting glucose uptake in some cancer cells. endothelial glucose metabolism has been recently connected to angiogenesis and it is now an emerging topic in scientific research. Indeed, certain compounds with a known effect on glucose metabolism have also been shown to inhibit angiogenesis. in this work we tested the capability of fasentin to modulate angiogenesis in vitro and in vivo. We show that fasentin inhibited tube formation in endothelial cells by a mechanism that involves a negative effect on endothelial cell proliferation and invasion, without affecting other steps related to the angiogenic process. However, fasentin barely decreased glucose uptake in human dermal microvascular endothelial cells and the GLUT-1 inhibitor STF-31 failed to inhibit tube formation in these cells. therefore, this modulatory capacity on endothelial cells function exerted by fasentin is most likely independent of a modulation of glucose metabolism. taken together, our results show a novel biological activity of fasentin, which could be evaluated for its utility in cancer and other angiogenesis-dependent diseases.
Keywords: Neovascularización; Tumour angiogenesis; Target identification